Presence of male mitochondria in somatic tissues and their functional importance at the whole animal level in the marine bivalve Arctica islandica - Cyril Dégletagne (Nature Portfolio, 2021)
Dégletagne et al. report on an unusual case of doubly uniparental inheritance in the ocean quahog, Arctica isladica. Some individuals in an Icelandic population present homoplasmic presence of male-type mitochondrial genes in somatic tissues, which appears to confer some changes in respiratory capacity in some environmental conditions.